The dietary inflammatory index and cardiometabolic parameters in US firefighters - Christodoulou, Andria; Christophi, Costas A.; Sotos-Prieto, Mercedes; Moffatt, Steven; Zhao, Longgang; Kales, Stefanos N.; Hébert, James R. (Frontiers in Nutrition, 2024)
Dietary choices play a crucial role in influencing systemic inflammation and the eventual development of cardiovascular diseases (CVD). The Dietary Inflammatory Index (DII®) is a novel tool designed to assess the inflammatory potential of one's diet. Firefighting, which is characterized by high-stress environments and elevated CVD risk, represents an interesting context for exploring the dietary inflammatory-CVD connection.Aim: This study aims to investigate the associations between Energy-adjusted Dietary Inflammatory Index (E-DII TM ) scores and cardiometabolic risk parameters among US firefighters.Methods: The study analyzed 413 participants from the Indianapolis Fire Department who took part in a Federal Emergency Management Agency (FEMA)-sponsored Mediterranean diet intervention trial. Thorough medical evaluations, encompassing physical examinations, standard laboratory tests, resting electrocardiograms, and submaximal treadmill exercise testing, were carried out. Participants also completed a detailed food frequency questionnaire to evaluate dietary patterns, and E-DII scores were subsequently computes based on the gathered information.Results: Participants had a mean body mass index (BMI) of 30.0 ± 4.5 kg/m 2 and an average body fat percentage of 28.1 ± 6.6%. RLinear regression analyses, adjusted for sex, BMI, maximal oxygen consumption (VO2 max), max metabolic equivalents (METS), age, and body fat percentage, revealed significant associations between high E-DII scores and total cholesterol (β=810.37.11, p=0.042). When comparing low Vs median E-DII scores there is an increase in glucose (β=0.91, p=0.72) and total cholesterol (β=5.51, p=0.26).For the unadjusted model BMI (β=1.38, p=0.002), body fat percentage (β=1.44, p=0.03) and cholesterol ratio (β=0.43, p=0.001) were significantly associated with E-DII scores Conclusion: Our findings support an association between higher E-DII scores and increasing adiposity, as well as worse lipid profiles.